First you write a sentence. : the elements of reading, writing...and life - Moran, Joe, 1970- (Penguin Books, 2019)
"The sentence is the common ground where every writer walks. A good sentence can be written (and read) by anyone if we simply give it the gift of our time, and it is as close as most of us will get to making something truly beautiful. Using minimal technical terms and sources ranging from the Bible and Shakespeare to George Orwell and Maggie Nelson, as well as scientific studies of what can best fire the reader's mind, author Joe Moran shows how we can all write in a way that is clear, compelling and alive. Whether dealing with finding the ideal word, building a sentence, or constructing a paragraph, First You Write a Sentence informs by light example: much richer than a style guide, it can be read not only for instruction but for pleasure and delight. And along the way, it shows how good writing can help us notice the world, make ourselves known to others, and live more meaningful lives. It's an elegant gem in praise of the English sentence"--